Recycling of polyurethane foam waste in the production of lightweight cement pastes and its irradiated polymer impregnated composites. Issue 4 (24th January 2019) - Abdel‐Rahman, H.A.; Younes, M.M.; Khattab, Magdy M.
Abstract : This study aimed at using polyurethane foam waste in the production of lightweight white cement pastes by a partial replacement of white cement with different ratios of polyurethane foam waste (10%, 20%, 30%, and 40%) based on the weight of cement. The lightweight white cement pastes specimens in addition to conventional white cement paste were cured under tap water for 7 and 28 days. The physical, mechanical, and thermal properties were evaluated. The results showed that the specimens cured for 28 days achieved better properties as compared to the specimens cured for 7 days. Furthermore, at each curing age the specimens of lightweight white cement pastes showed relatively lower properties as compared to the conventional white cement paste and as the polyurethane waste content increased, the properties in terms of compressive strength and bulk density decreased while the total porosity percentage increased especially at higher ratios. On the other hand, the effects of styrene–butadiene rubber latex and irradiation dose on the properties of irradiated polymer impregnated lightweight white cement composites have been investigated. The results confirmed that the impregnation of the hardened lightweight white cement pastes with styrene–butadiene rubber latex and their exposure to different doses of gamma rays (50, 100, 150, and 200 kGy) showed a gradual improvement in the mechanical and physical properties up to 150 kGy and then started to decrease at 200 kGy. Characterization of some selected specimens was carried out by the studying of thermogravimetric analysis, scanning electron microscopy, and X‐ray diffraction. J. VINYL ADDIT. TECHNOL., 25:328–338, 2019. © 2019 Society of Plastics Engineers